The impact of under-recording on cervical cancer-related mortality rates in colombia: an equity analysis involving comparison by provenance (2012)
Objective Comparing cervical cancer mortality rates in Colombian departments, as well as in urban and rural areas and examining the potential causes of any differences.Methodology This was an ecologic study. Mortality due to cervical cancer was estimated from data collected between 2005 and 2008 by the Colombian National Statistics Bureau (DANE).This included overall mortality in Colombia, mortality by department and mortality by rural and urban area. DANE provided theunder-recording indicator for mortality by departments and the unmet basic needs index. Spearman correlation coefficient was estimated for average mortality by department, unmet basic needs and under-recording variables.Results The overall annual mortality rate from 2005 to 2008 due to cervical cancer in Colombia ranged from 10 to 11.1 per 100,000 females. Mortality reported in urban areas was higher than in rural areas (10.3-11.7 cf 7.6-8.7). The lowest average mortality was reported from the Chocó department (4.7) and the highest from Meta (18.2). An inverse correlation was found between average mortality by department and unmet basic needs. The ‘under-reporting’ indicator had an inverse correlation with mortality, meaning that departments having recording issues also reported lower mortality rates.Conclusions Health systems must adopt strategies designed to improve information systems for supporting decision-making and optimise the use of health resources, particularly for vulnerable populations and populations having unmet basic needs. Comparing mortality amongst departments and areas will not lead to reliable conclusions in such under-recording conditions.Key Words: Uterine cervical neoplasm, mortality, needs assessment, disease notification (source: MeSH, NLM).